Managing diabetes, managing medicine Chronic disease and clinical bureaucracy in post-war Britain - Moore, Martin D. (Social Histories of Medicine, 2019)
Through a study of diabetes care in post-war Britain, this book is the first historical monograph to explore the emergence of managed medicine within the National Health Service. Much of the extant literature has cast the development of systems for structuring and reviewing clinical care as either a political imposition in pursuit of cost control or a professional reaction to state pressure. By contrast, Managing Diabetes, Managing Medicine argues that managerial medicine was a co-constructed venture between profession and state. Despite possessing diverse motives - and though clearly influenced by post-war Britain's rapid political, technological, economic, and cultural changes - general practitioners (GPs), hospital specialists, national professional and patient bodies, a range of British government agencies, and influential international organisations were all integral to the creation of managerial systems in Britain. By focusing on changes within the management of a single disease at the forefront of broader developments, this book ties together innovations across varied sites at different scales of change, from the very local programmes of single towns to the debates of specialists and professional leaders in international fora. Drawing on a broad range of archival materials, published journals, and medical textbooks, as well as newspapers and oral histories, Managing Diabetes, Managing Medicine not only develops fresh insights into the history of managed healthcare, but also contributes to histories of the NHS, medical professionalism, and post-war government more broadly.